ANALYSIS THE ROLE OF NEGOTIATION AS COMMUNICATION SKILLS IN CONFLICT MANAGEMENT - Reza Inayaturrahmah; Cecep Safaatul Barkah; Nurillah Jamil Achmawati Novel (Universitas Muhammadiyah Yogyakarta, 2022)
Negotiation is not a new term. This negotiation is one form of communication. This negotiation becomes one of the means for both parties or more who experience disputes in an effort to achieve their respective goals. Moreover, in everyday life, there are conflicts and differences in interests that are very common. This study aims to analyze the role of negotiation as a communication skill in conflict management. This study refers to the literature review as a source of information that will then be reviewed, studied, understood, and interpreted on the data and information obtained from the reference sources used. The results of this study indicate that negotiation, especially integrative negotiation, has an essential role as a peaceful conflict resolution in conflict management, both parties can communicate directly and seek mutual agreement. Good communication skills really help the negotiation process achieve maximum results even from negotiations will be able to create good business opportunities. The important role of this negotiation is not only used in resolving business conflicts but in other aspects so that problems can be resolved wisely and fairly without harming either party.